Relationship of the CD5 B cell to human tonsillar lymphocytes that express autoantibody-associated cross-reactive idiotypes. - Kipps, T J (1991)
We examined human tonsillar B cells for expression of autoantibody heavy-chain or kappa light-chain cross-reactive idiotypes (CRIs), respectively defined by murine MAbs G6 or 17.109. We find 17.109 or G6 each specifically binds a subpopulation of B cells, respectively reacting with 3.8 +/- 3% (mean +/- SD) or 2.0 +/- 1.2% of all tonsillar lymphocytes. Cells reactive with both 17.109 and G6 comprise only 0.4 +/- 0.3% of tonsillar lymphocytes. Although each tested specimen had 17.109-positive cells, 2 of 19 tonsils (11%) did not have any G6-reactive cells. We find that CRI-positive cells and CD5 B cells both co-express slgD but fail to bind peanut agglutinin or MAbs specific for CD10, indicating that both cell types reside in the mantle zones of secondary B cell follicles. However, less than half of the B cells bearing one or both of these CRIs express detectable levels of CD5. Nevertheless, we find that G6-reactive lymphocytes constitute a multiclonal population of cells that express homologous heavy chain variable region genes, each rearranged to one of several distinct and apparently nonmutated D and JH gene segments. Collectively, these studies indicate that expression of nondiversified autoantibody-encoding variable region genes may not be an exclusive property of B cells that bear detectable levels of the CD5 surface antigen.